PENGARUH PENERAPAN METODE PEMBELAJARAN AKTIF TIPE TEAM QUIZ DISERTAI HANDOUT TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMA N 1 TALAMAU - Gina, Arisya - (STKIP PGRI Sumbar, 2014)
This research is inspired by This research is inspired by studentsâ low learning outcome onbiology studentsâ in material reproduction XI grade science at SMAN 1 Talamauin academic year2012/2013. One of alternative method that improve studentsâ learning outcome is by implementingactive learning method on type team quiz with handout. This research aims to know about theeffect of implementing active learning team quiz type with handout toward studentsâ learningoutcome on material system reproduction at SMAN 1 Talamau. Type of this research wasexperimental research and research design was Randomized Control Group Posttest OnlyDesign,technique of data collection was purposive sampling. Researchâs result can be seen thatexperimental class had average score more higher than control class which is amount tcount=4,1 andamount ofttable=1,67 so that tcount>ttable therefore hypotheses accepted. So, it can be conclude thatimplementing of Active Learning Method team quiz type with handout able to improve studentâlearning X1 grade science at SMAN 1 Talamau.